Multilayer NiO@Co3O4@graphene quantum dots hollow spheres for high-performance lithium-ion batteries and supercapacitors. Issue 13 (14th March 2019) - Yin, Xiaojie; Zhi, Chuanwei; Sun, Weiwei; Lv, Li-Ping; Wang, Yong
Abstract : Multilayer NiO@Co3 O4 hollow spheres are modified by graphene quantum dots and exhibit superior performances for lithium-ion batteries and supercapacitors. Abstract : In the present study, we designed and prepared multilayer NiO@Co3 O4 hollow spheres decorated with graphene quantum dots (NiO@Co3 O4 @GQDs) through a rational solvothermal treatment. The decoration of the GQDs endowed the hybrid structure with excellent electrochemical behaviors in lithium-ion batteries (LIBs) and supercapacitors (SCs). The core–shell NiO@Co3 O4 hollow structure was designed based on the stepwise lithium storage mechanism (first in the Co3 O4 shell and then in the NiO core). The carboxyl-functionalized GQDs led to reduced interfacial resistance and increased surface area for electrochemical reactions. The high polarity of the carboxyl functionalized GQDs also showed a strong affinity to the Li + in LIBs and K + /OH − in SCs. As an anode for LIBs, it demonstrated a large reversible capacity of 1158 mA h g −1 (NiO@Co3 O4 contribution: ∼1327 mA h g −1 ) after 250 cycles at 0.1 A g −1 . As a SC cathode, it held an impressive high specific capacitance of 1361 F g −1 (748.5 C g −1 ) at 1 A g −1, and retained 76.4% capacitance after 3000 cycles. Moreover, the assembled all-solid-state asymmetric supercapacitors (ASCs) (NiO@Co3 O4 @GQDs//AC) could deliver an energy density of 38.44 W h kg −1 and a superior cyclability (84.3% retention after 10 000 cycles).